학술지 평가제도와 관리체계에 관한 연구 - 쟁점과 개선방안 - 서문기(Suh, Moon-Gi) (문화콘텐츠연구, 2021)
최근 국내 학술지의 과도한 양적 성장이 학술지 관리에 대한 정량 및 형식 위주의평가체계 등 심각한 부작용을 수반하게 되었다는 점을 고려할 때, 등재학술지 관리체계에 대한 보완이 시급하다. 아울러 학술지 평가의 중요성에도 불구하고 이에 관한 선행연구가 적을뿐더러 체계적인 연구 설계와 경험적인 연구에 기초한 평가모델의 제시나 깊이 있는 통찰이 크게 부재한 상황이다. 이에 본 연구는 학술지의 평가기준과 방법의 문제점에 대하여 체계적으로 진단하고 실증적인 분석 결과를 통해평가제도의 개선방안을 제시한다. 학술지 평가의 본질은 다음과 같은 두 가지 명제를 대전제로 한다. 첫째, 학술지 평가는 연구 환경의 자율적 통제를 위한 것이어야한다. 둘째, 학술지 평가의 원칙은 연구 활동의 책무성에 기초한 질적 제고이며 평가 기준의 문제점을 분석하고 연구의 수월성 및 부가가치를 효과적으로 생산해야한다. 다중회귀분석 결과는 연간 발행 횟수, 등재 유지 기간, 유료회원 수, KCI 등이등재학술지 평가에서 중요한 결정요인임을 보여주며 평가체계가 양적 중심에서질적 중심으로 전환하는 계기를 제공한다. 학술지 평가의 목적이 연구의 질적 수준을 평가하여 대외경쟁력과 신뢰를 향상하는 데 있다면, 이러한 목적이 실질적으로성취되었는지를 타당하게 판단할 수 있는 기준들을 특성별로 상세하게 설계하여체계적으로 마련할 필요가 있다. The recent excessive quantitative expansion of academic journals entailsserious side effects such as simplicity and formality for resource management,which allows the evaluation system to be revised. Although the relevantissues are critical, there are few previous studies which can produceevaluation models and in-depth insight by systematic research design orempirical analysis. Against this backdrop, the present study systematicallydiagnoses the problems of evaluation criteria and evaluation methods forjournals, and suggests appropriate ways to reform the evaluation system. The essence of journal evaluation is premised on the following twopropositions: First, it requires autonomous control of the research milieu. Second, academia is in pursuit of qualitative improvement and accountabilityof research activities, which effectively guarantee research excellence andadded value. Multiple regression results identify the number of annualpublications, the period of registration, the number of paid members, andthe KCI as the critical determinants of journal evaluation, which provide anopportunity to convert quantitative to qualitative one. If the goal of journalmanagement is to increase competitiveness and trust by determine whether these objectives are being substantially achieved aredesigned in detail for its own color. evaluating thequality of research, the standards based on the rationale that can reasonably determine whether these objectives are being substantially achieved are designed in detail for its own color. KCI Citation Count: 0